Intracellular antibody targeting HBx suppresses invasion and metastasis in hepatitis B virus‐related hepatocarcinogenesis via protein phosphatase 2A‐B56γ‐mediated dephosphorylation of protein kinase B. Issue 11 (10th July 2022) - Che, Lin; Du, Ze‐Bang; Wang, Wei‐Hua; Wu, Jia‐Shen; Han, Tun; Chen, Yuan‐Yuan; Han, Pei‐Yu; Lei, Zhao; Chen, Xiao‐Xuan; He, Yun; Xu, Ling; Lin, Xu; et al.
Abstract: Objectives: Hepatitis B virus X (HBx) is closely associated with HBV‐related hepatocarcinogenesis via the inactivation of tumour suppressors. Protein phosphatase 2A (PP2A) regulatory subunit B56 gamma (B56γ), as a tumour suppressor, plays a critical role in regulating cellular phosphorylation signals via dephosphorylation of signalling proteins. However, the underlying mechanism that B56γ involved in regulating HBx‐associated hepatocarcinogenesis phenotypes and mediating anti‐HBx antibody‐mediated tumour suppression remains unknown. Materials and Methods: We used bioinformatics analysis, paired HCC patient specimens, HBx transgenic (HBx‐Tg) mice, xenograft nude mice, HBV stable replication in the HepG2.2.15 cells, and anti‐HBx antibody intervention to systematically evaluate the biological function of protein kinase B (AKT) dephosphorylation through B56γ in HBx‐associated hepatocarcinogenesis. Results: Bioinformatics analysis revealed that AKT, matrix metalloproteinase 2 (MMP2), and MMP9 were markedly upregulated, while cell migration and viral carcinogenesis pathways were activated in HBV‐infected liver tissues and HBV‐associated HCC tissues. Our results demonstrated that HBx‐expression promotes AKT phosphorylation (p‐AKT Thr308/Ser473 ), mediating the migration and invasion phenotypes in vivo and in vitro. Importantly, in clinical samples, HBx and B56γ were downregulated in HBV‐associated HCC tumour tissues compared with peritumor tissues. Moreover, intervention with site‐directed mutagenesis (AKT T308A, AKT S473A ) of p‐AKT Thr308/Ser473 mimics dephosphorylation, genetics‐based B56γ overexpression, and intracellular anti‐HBx antibody inhibited cell growth, migration, and invasion in HBx‐expressing HCC cells. Conclusions: Our results demonstrated that B56γ inhibited HBV/HBx‐dependent hepatocarcinogenesis by regulating the dephosphorylation of p‐AKT Thr308/Ser473 in HCC cells. The intracellular anti‐HBx antibody and the activator of B56γ may provide a multipattern chemopreventive strategy against HBV‐related HCC. Abstract : Schematic diagram of PP2A‐B56γ mediated the dephosphorylation of p‐AKT Thr308/Ser473 in HBx‐expressing HCC cells to regulate the migration and invasion phenotypes of HBV/HBx‐related hepatocarcinogenesis. In current study, HBx‐expression induced the phosphorylation of specific AKT sites (p‐AKT Thr308/Ser473 ) involved in mediating the migration and invasion phenotypes of HCC cells. The inducible upregulation of B56γ mediated the dephosphorylation of p‐AKT Thr308/Ser473 in HBx‐expressing HCC cells. Specific blockade of HBx‐expression via pTT5‐anti‐HBx plasmid‐mediated targeting intracellular anti‐HBx mAb production and genetic activation of B56γ would help to target the p‐AKT Thr308/Ser473 ‐MMP2/9 signalling axis to mediate the multipattern chemoprevention and intervention in HBV/HBx‐related hepatocarcinogenesis.